The Contribution of Parents Involvement towards Students’ Academic Performance at Ugandan Certificate of Education in Public Secondary - Alfred, Mugomba; Kiggundu, Ssegawa E James; Musa, Muwaga; Wamaungo, Juma Abdu (Journal of Social Work and Science Education, 2023)
The research aimed to evaluate parental influence on students' academic achievement in high school. It investigated academic performance, parental involvement, and their impact on secondary school students. Using a cross-sectional survey with 357 participants including head teachers, teachers, students, and BOG members, a self-administered questionnaire was utilized. Results indicated 80-89% score improvements in reading and writing skills, though fluency requires over 90%. Homework had 80-98% accuracy, but stronger focus was needed. Poor concentration and attendance highlighted the necessity for more support. Students struggled with question comprehension and irregular achievement. Parental engagement in health programs scored neutrally, signaling a need for increased involvement. Involvement in learning-related responsibilities was hindered by behavioral issues. Positive correlations existed between parental engagement and academic success, including safety, diversity, and regulatory aspects. Writing materials positively impacted, while reading materials showed a decline. Counseling services exhibited a weak correlation. Overall, parental involvement significantly predicted UCE students' academic improvement (B = 0.502; p = .000 < 0.05), contributing to 50.2% positive changes.